PENGEMBANGAN APLIKASI ANDROID BERBANTU SOFTWARE ISPRING SUITE SEBAGAI MEDIA PEMBELAJARAN EKONOMI MADRASAH ALIYAH MA’ARIF 9 KOTAGAJAH TAHUN PELAJARAN 2018/2019 - Novita Anggestia; Triani Ratnawuri; Meyta Pritandhari (Universitas Muhammadiyah Metro, 2021)
Learning media is one of the needs that must be fulfilled in the learning process. The results of the pre-survey of learning media used in the Aliyah Ma'arif 9 Kotagajah Madrasah, researchers found several problems, namely the use of learning media that were less innovative in learning and the limitation of images in teaching books, worksheets and powerpoints so that students were not attracting attention in the learning process . So that learning media are needed that can attract the attention of students such as android applications, android application software assisted ispring suite as an economic learning media arranged concisely, clearly, and made in a practical form so that students are more interested and enthusiastic in learning and can understand the material. The development model used in this development is the ADDIE development model which consists of several stages, namely (Analysis, Design, Development, Implementation, and Evaluation). Based on the results of the development of android applications assisted by software ispring suite as an economic learning media it is known the results of recapitulation of data that have been carried out by learning media material experts on android applications with an average score of 86% included in the very feasible category and declared valid, the results of recapitulation from media experts with scores on average 87% fall into the category of very decent and declared valid. Furthermore, the practicality test by IPS X grade 1 students of Aliyah Ma'arif 9 Kotagajah gets an average score of 92.2% and falls into the very practical category so that it is declared practical. research shows that economic learning media using this android application is suitable for use in learning. Thus it can be concluded that the learning media of android applications are learning media that are valid and practical to be used in the learning process.